2022
DOI: 10.31083/j.rcm2310343
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Assessment of Prosthetic Valves

Abstract: Prosthetic valves are increasingly encountered in clinical practice. A grasp of the intricacies of the assessment and management of prosthetic valves is thus a crucial skillset for the practicing cardiologist. Echocardiography is the imaging modality of choice for the anatomic and functional evaluation of prosthetic valve. This document reviews the general features of prosthetic valves, echocardiographic identification of normally functioning and dysfunctional prosthetic valves as well as echocardiographic dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…TTE can define abnormal valvular hemodynamics, but TEE is superior in clarifying the precise etiology responsible for valve dysfunction [ 10 ]. An algorithmic approach has been suggested when evaluating mitral valve prosthesis with echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…TTE can define abnormal valvular hemodynamics, but TEE is superior in clarifying the precise etiology responsible for valve dysfunction [ 10 ]. An algorithmic approach has been suggested when evaluating mitral valve prosthesis with echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…The hemodynamic profile of normally functioning stented AV protheses resembles that of mild native aortic stenosis with slightly elevated mean transvalvular gradients and peak transvalvular velocities. 20,21 In contrast, native valve-preserving procedures offer the potential benefit of postoperative transvalvular hemodynamics similar to those of wellfunctioning native valves due to the absence of a rigid stent and sewing ring and preserved native aortic root geometry allowing for preserved transvalvular flow characteristics and LV dynamics. 22 Romeo et al reported excellent hemodynamics across the autograft following the Ross procedure in an international multicenter study of 1,063 patients.…”
Section: Commentmentioning
confidence: 99%